(untitled) (PJDOL, 2023)
This study was an experimental design research. It aim was to evaluate the effectiveness of simulation in teaching of Physics at higher secondary school level. The main objective of the study was to explore the effect of simulation method of teaching Physics on academic achievement of students. Achievements were compared, taught by simulation method and conventional lecture method.